Pediatric zoster: two cases and a review of the literature on the changing epidemiology of herpes zoster. - Kollipara, R.; Downing, C.; Curtis, S.; Tyring, S. (European Journal of Pediatric Dermatology, 2014)
The advent of the varicella and herpes zoster vaccines has sparked debate on whether vaccination will decrease the age of incidence of herpes zoster (HZ). Studies thus far have been inconclusive in determining if the epidemiology of HZ is changing. Here we present two cases of HZ in two-year-old healthy children as well as an analysis of the mean age of onset of 1,000 patients seen in our clinic between 2010 and 2013 with HZ. Our analysis revealed the mean age of HZ onset to be 51.5 years in the last 4 years, which is lower than the mean age reported in the literature. Although this datum is not conclusive, it does add to the literature showing that the average age of HZ onset is decreasing and thus clinicians should be vigilant in detecting HZ in younger patients.